Livestock farmers mobilization as a contribution towards developing a sustainable livelihood among subsistence farmers : case study of Gideon Cluster at Eldorado Agricultural Service Centre, Blouberg Municipality - Mudzielwana, Ofhani Freddy (My University, 2014)
This study sets out to evaluate the outcomes of an institutional intervention to mobilize livestock owners in the Gideon Cluster of Blouberg Municipality of Capricorn District in Limpopo Province. The intervention from the Limpopo Department of Agriculture was in response to the declaration of the study area as a poverty nodal area. Further, smallholder livestock keeping is an important feature of the agricultural landscape. However smallholder land users are poorly organized and essentially utilize natural resources under systems of open access, meaning that there are no community rules that regulate access to and utilization of natural resources. This leads to veld degradation, forage shortages during the post winter period and droughts and regularly results in catastrophic livestock mortalities which represent a huge economic investment. The researcher had a leading role in this mobilization effort and a keen interest to evaluate the outcomes thereof. A questionnaire survey and semi structured interviews were conducted to assess the perceptions of livestock owners in the study area on a range of topics and subtopics. The aim was to answer the following research questions: (i) Who are the key role players in the mobilization of the farmers? (ii) What was the success rate of the approaches used to mobilize the farmers? (iii) What was the extent of the contribution brought by farmers’ mobilization to sustainable livelihoods at the Cluster? (iv) To what extent did farmers network amongst themselves?The study found that the LDA intervention succeeded in unifying the livestock owners in the study area to function to a certain degree as a team, working together towards shared objectives and to solve problems. Stock theft for instance reduced dramatically and veld utilization improved. These improvements together with the fact that farmers continued to arrange and hold problem solving meetings were regarded as evidence that the approaches used in the mobilization process were effective and produced positive social outcomes. With regards to livelihood improvement no clear indicators could be established. However the study found that livestock owning households did more readily sell livestock at organized livestock auctions. Previously livestock owners were exploited by speculators, livestock buyers exchanging goats and sheep for wheelbarrows and sheets of corrugated iron. The study found that farmers were networking amongst themselves through independently run meetings and collective decision making. This study concluded that the mobilization process initiated by LDA was successful and had positive social outcomes. This allowed the study to recommend that the mobilization process could be used to mobilize smallholders towards greater self sufficiency, towards solving their problems and to improve the livelihood benefits from their smallholder enterprises.
Thesis (M. A. (Agricultural Extension) -- University of Limpopo, 2014
Keywords: Subsistence farmers; Livestock owners; Mobilization of the farmers; Livestock breeders -- South Africa; Livestock -- Effect of drought on; Farmers -- Training of -- South Africa -- Limpopo